A West Point Treasure; Or, Mark Mallory's Strange Find - Sinclair, Upton, 1878-1968 (Salt Lake City, UT : Project Gutenberg, 2021)
"A West Point Treasure; Or, Mark Mallory's Strange Find" by Upton Sinclair is a novel written in the early 20th century. The story revolves around the adventures of Mark Mallory and his group of friends, known as the Banded Seven, who are cadets at West Point Military Academy. This tale intertwines elements of mystery, camaraderie, and humor as they embark on thrilling escapades, including an unexpected discovery in a hidden cave. At the start of the novel, we are introduced to Mark Mallory, a bold cadet known for defying upperclassmen. He shares a letter from Wicks Merritt, warning of potential trouble but also relaying gossip about their antics, which has garnered attention. The Banded Seven, including characters like Texas and the Parson, find themselves inspired by the letter to explore the nearby mountains. Their exploration leads to the astonishing discovery of a cave, where they soon encounter signs of previous inhabitants$1 (Ba cache of counterfeit coins and the unsettling remnants of skeletons$1 (Bsetting the stage for a thrilling adventure as they grapple with the mysteries and dangers that lie ahead. (This is an automatically generated summary.)s
Release date is 2021-02-22
E-text prepared by D A Alexander, David E. Brown, and the Online Distributed Proofreading Team (https://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Conduct of life -- Juvenile fiction; Adventure stories; Friendship -- Juvenile fiction; Revenge -- Juvenile fiction; Treasure troves -- Juvenile fiction; Students -- Juvenile fiction; Youth -- Conduct of life -- Juvenile fiction; Soldiers -- Juvenile fiction; Courage -- Juvenile fiction; Thieves -- Juvenile fiction; Fires -- Juvenile fiction; United States Military Academy -- Juvenile fiction